Focused ultrasound treatment of abscesses induced by methicillin resistant Staphylococcus aureus: Feasibility study in a mouse model. Issue 6 (15th May 2014) - Rieck, Birgit; Bates, David; Zhang, Kunyan; Escott, Nicholas; Mougenot, Charles; Pichardo, Samuel; Curiel, Laura
Abstract : Purpose: To study the therapeutic effect of focused ultrasound on abscesses induced by methicillin‐resistant Staphylococcus aureus (MRSA). MRSA is a major nosocomial pathogen where immunocompromised patients are prone to develop infections that are less and less responsive to regular treatments. Because of its capability to induce a rise of temperature at a very precise location, the use of focused ultrasound represents a considerable opportunity for therapy of localized MRSA‐related infections. Methods: 50 μ l of MRSA strain USA400 bacteria suspension at a concentration of 1.32 ± 0.5 × 10 5 colony forming units (cfu)/ μ l was injected subcutaneously in the left flank of BALB/c mice. An abscess of 6 ± 2 mm in diameter formed after 48 h. A transducer operating at 3 MHz with a focal length of 50 mm and diameter of 32 mm was used to treat the abscess. The focal point was positioned 2 mm under the skin at the abscess center. Forty‐eight hours after injection four ultrasound exposures of 9 s each were applied to each abscess under magnetic resonance imaging guidance. Each exposure was followed by a 1 min pause. These parameters were based on preliminary experiments to ensure repetitive accurate heating of the abscess. Real‐time estimation of change of temperature was done using water‐proton resonance frequency and a communication toolbox (matMRI) developed inhouse. Three experimental groups of animals each were tested: control, moderate temperature (MT), and high temperature (HT). MT and HT groups reached, respectively, 52.3 ± 5.1 and 63.8 ± 7.5 °C at the end of exposure. Effectiveness of the treatment was assessed by evaluating the bacteria amount of the treated abscess 1 and 4 days after treatment. Myeloperoxidase (MPO) assay evaluating the neutrophil amount was performed to assess the local neutrophil recruitment and the white blood cell count was used to evaluate the systemic inflammatory response after focused ultrasound treatment. Results: Macroscopic evaluation of treated abscess indicated a diminution of external size of abscess 1 day after treatment. Treatment did not cause open wounds. The median (lower to upper quartile) bacterial count 1 day after treatment was 6.18 × 10 3 (0.76 × 10 3 –11.18 × 10 3 ), 2.86 × 10 3 (1.22 × 10 3 –7.07 × 10 3 ), and 3.52 × 10 3 (1.18 × 10 3 –6.72 × 10 3 ) cfu/100 μ l for control, MT and HT groups, respectively; for the 4‐day end point, the count was 1.37 × 10 3 (0.67 × 10 3 –2.89 × 10 3 ), 1.35 × 10 3 (0.09 × 10 3 –2.96 × 10 3 ), and 0.07 × 10 3 (0.03 × 10 3 –0.36 × 10 3 ) cfu/100 μ l for control, MT and HT, showing a significant reduction (p = 0.002) on the bacterial load four days after focused ultrasound treatment when treating at high temperature (HT). The MPO amount remained unchanged between groups and days, indicating no change on local neutrophil recruitment in the abscess caused by the treatment. The white blood cell count remained unchanged between groups and days indicating that no systemic inflammatory response was caused by the treatment. Conclusions: Focused ultrasound induces a therapeutic effect in abscesses induced by MRSA. This effect is observed as a reduction of the number bacteria without significantly altering the amount of MPO at the site of a MRSA‐induced abscess. These initial results suggest that focused ultrasound is a viable option for the treatment of localized MRSA‐related infections.